2014
DOI: 10.3762/bjnano.5.169
|View full text |Cite
|
Sign up to set email alerts
|

Growth and structural discrimination of cortical neurons on randomly oriented and vertically aligned dense carbon nanotube networks

Abstract: SummaryThe growth of cortical neurons on three dimensional structures of spatially defined (structured) randomly oriented, as well as on vertically aligned, carbon nanotubes (CNT) is studied. Cortical neurons are attracted towards both types of CNT nano-architectures. For both, neurons form clusters in close vicinity to the CNT structures whereupon the randomly oriented CNTs are more closely colonised than the CNT pillars. Neurons develop communication paths via neurites on both nanoarchitectures. These neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…We begin by reviewing the herding properties of the retinal cells on the Euclidean electrodes. The large neuronal process lengths observed on the electrodes is consistent with previous results [ 77 ] and can be explained in part by the VACNTs’ favorable surface texture: their nano-scale roughness ( S1b and S1c Fig ) has been proposed to mimic some of the ECM properties [ 91 , 92 ] and to enhance neurite outgrowth and elongation if the roughness variation matches the process diameter [ 93 ]. VACNT flexibility also likely plays a role since neurons are known to readily adhere to and grow processes on softer substrates [ 94 , 95 ].…”
Section: Discussionsupporting
confidence: 86%
“…We begin by reviewing the herding properties of the retinal cells on the Euclidean electrodes. The large neuronal process lengths observed on the electrodes is consistent with previous results [ 77 ] and can be explained in part by the VACNTs’ favorable surface texture: their nano-scale roughness ( S1b and S1c Fig ) has been proposed to mimic some of the ECM properties [ 91 , 92 ] and to enhance neurite outgrowth and elongation if the roughness variation matches the process diameter [ 93 ]. VACNT flexibility also likely plays a role since neurons are known to readily adhere to and grow processes on softer substrates [ 94 , 95 ].…”
Section: Discussionsupporting
confidence: 86%
“…As stated earlier, VACNTs have much higher surface areas, better charge injection capability, and patternability, thus making them more suitable as electrodes, which can self-assemble neural networks. This same conclusion was presented by Nick et al and supports that VACNTs can be used to culture neuron cells and simultaneously stimulate and record their action potentials …”
Section: Biomedical Applicationssupporting
confidence: 83%
“…Those findings are in agreement with previous studies using cortical neurons which showed that neither the vertically aligned dense carbon nanotube networks nor the respective biomaterials used during the generation of the MWCNT showed toxic effects on neurons. 45 Consequently, we propose that toxic effects of MWCNT can be excluded as a reason for the strong inhibition of biofilm formation observed in our study.…”
Section: Inhibition Of Biofilm Formation By Nanotubes: Possible Mechamentioning
confidence: 57%